Models and methods for multicriterial optimization tasks - Зіатдінов, Ю. К.; Климова, А. С. (Problems of Informatization and Control, 2005)
The various approaches of vector optimization problem decision are considered. The analysis of opportunities and application experience of various models and mathematical methods of the optimum problems decision are given